PERANCANGAN APLIKASI E-PRESENSI SISWA SEKOLAH MENENGAH DI KOTA PEKALONGAN BERBASIS ANDROID - Mulyani, Esti; Maulana, Much. Rifqi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Mean Years Schooling (MYS) of the population of Pekalongan City in the past 4 (four) years has increased, although slowly. One factor that makes the average length of schooling is the level of student attendance. When students are rarely present at school, the student will miss the learning material so that his performance decreases. Students whose achievement is below average usually will not continue their education to a higher level. This research intends to develop an application e-Presensi to monitor the presence of secondary school students in Pekalongan City. With the e-Presensi application, students attend school using finger print. The system will send messages on the parent / guardian smartphone (client side, so parents / guardians can easily monitor thepresence of their children in school. Schools are also easier to recap student attendance at the end of the semester. By using this e-Presence, It is expected to increase student attendance and reduce school skipping rates, so that in the long run it can increase Mean Years Schooling (MYS) of Pekalongan City residents. Keywords: Android application, e-Presensi, student attendance